Hydrogeochemistry of the Umm er Radhuma Unconfined Aquifer, Western Desert Iraq- Saudi border - Kadum, Weam Hassan (Iraqi Journal of Science, 2022)
The Umm Er Radhuma unconfined aquifer Hydrogeochemistry in the Saudi – Iraq border desert was studied to identify the main hydrogeochemical processes and rock-water interaction. The measurements were done using standard APHA procedures. The results indicated that Na+ and Cl- are the dominant ions in the groundwater. The average contribution of cations in the aquifer is Na+ + K+ ( 26 %), Ca2+ (14 %), and Mg2+ (10%) ; whereas anions contribution is Cl- (24 %) , SO42- (20 %), and HCO3- (6 %).  The results reflect that the examined water is hard water of neutral to slightly alkaline, slightly brackish, with mineralized pH conditions. The main conclusion of chemical reactions indicated carbonates, evaporate dissolution, and clay minerals water interaction through ionic exchanging.